2017
DOI: 10.1371/journal.pone.0172107
|View full text |Cite
|
Sign up to set email alerts
|

Remote-sensing based approach to forecast habitat quality under climate change scenarios

Abstract: As climate change is expected to have a significant impact on species distributions, there is an urgent challenge to provide reliable information to guide conservation biodiversity policies. In addressing this challenge, we propose a remote sensing-based approach to forecast the future habitat quality for European badger, a species not abundant and at risk of local extinction in the arid environments of southeastern Spain, by incorporating environmental variables related with the ecosystem functioning and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Several studies e.g. [ 35 , 50 , 110 , 116 ], and our results, have confirmed that remotely sensed variables related to ecosystem functioning (e.g. EFAs) can be useful predictors for modelling protected species distribution and habitat suitability.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Several studies e.g. [ 35 , 50 , 110 , 116 ], and our results, have confirmed that remotely sensed variables related to ecosystem functioning (e.g. EFAs) can be useful predictors for modelling protected species distribution and habitat suitability.…”
Section: Discussionsupporting
confidence: 86%
“…Overall, our results confirmed the known predictive ability of the satellite-derived EFAs at coarse resolutions [ 35 ], and expanded it to finer scales, even at the protected area level. This provides a local scale refined prediction of species potential distribution and habitat suitability that is closer to the scale required for management actions [ 6 , 109 , 110 ]. Such predictions could be further improved thanks to the availability of EFAs at even finer spatial resolutions (e.g., MODIS at ~250 m, LANDSAT at ~30m or Sentinel-2A at ~10m) and higher temporal resolutions (MODIS or the combination of LANDSAT plus Sentinel-2A), which is still a major constraint when using climate interpolated surfaces and land-cover data [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we applied species distribution models, also known as habitat suitability models, a technique that combines information on species occurrence or abundance with environmental estimates and/or spatial characteristics [21][22][23] . Species distribution models are mainly used to address the potential effects of climate change on species distribution [24][25][26] but are also used to improve the understanding of ecological factors for conservation planning and to detect unknown potential distribution areas for rare species [27][28][29] . Our goal is to identify the main ecological features of the southernmost subset of the Cuvier's Gazelle population in the Sahara; for this purpose, we integrated data from a broad-scale field survey carried out from 2011 to 2014 and species distribution models to model habitat selection at the landscape scale, using a predictive distribution map.…”
mentioning
confidence: 99%
“…In fact, satellite-derived EFAs are being also tested as candidate EBVs related to the carbon cycle, energy, and radiation balance capable of informing about ecosystem components linked to species conservation status [26,27]. Thus, the incorporation of EFAs into SDMs was found to increase their predictive power and transferability [28], offering the opportunity to cost-effectively monitor multiple endangered species [27,29], at different spatial and temporal scales [30]. Still, despite these advantages, the predictive ability of EFAs in abundance models as well as to assess inter-annual population dynamics of rare species remains largely untested.…”
Section: Introductionmentioning
confidence: 99%